Composite lithium cobalt oxide positive electrode material, preparation method thereof, positive electrode plate and lithium ion battery

By finely controlling the mixing ratio and sequence of lithium cobalt oxide and titanium aluminum lithium phosphate, a composite lithium cobalt oxide positive electrode material was prepared, which solved the problem that existing materials were difficult to take into account both energy density and rate performance, and achieved high density, high specific surface area and excellent electrochemical performance.

CN119725480AActive Publication Date: 2025-03-28EVE ENERGY CO LTD

Patent Information

Application Number
CN202411944656.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The existing lithium cobalt oxide cathode materials are difficult to take into account high energy density and excellent rate performance.

Method used

By finely controlling the mixing ratio and sequence of lithium cobalt oxide and titanium aluminum phosphate, composite lithium cobalt oxide positive electrode material is prepared to optimize its particle size distribution and physical properties.

Benefits of technology

The composite lithium cobalt oxide positive electrode material has achieved high density and high specific surface area, significantly improving the energy density of lithium-ion batteries, and improving its recycling life at high magnifications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005214917790000161
    Figure BDA0005214917790000161
  • Figure BDA0005214917790000171
    Figure BDA0005214917790000171
Patent Text Reader

Abstract

The invention provides a composite lithium cobalt oxide positive electrode material, a preparation method thereof, a positive electrode plate and a lithium ion battery. The composite lithium cobalt oxide positive electrode material comprises first lithium cobalt oxide of which the D50 is 13-16 [mu] m, second lithium cobalt oxide of which the D50 is 5.5-6.5 [mu] m, first titanium aluminum lithium phosphate of which the D50 is 300-500 nm and second titanium aluminum lithium phosphate of which the D50 is 100-280 nm, the weight ratio of the first lithium cobalt oxide to the first lithium titanium aluminum phosphate is (100-300): 1; the weight ratio of the second lithium cobalt oxide to the second lithium titanium aluminum phosphate is (100-300): 1; the weight ratio of the first lithium cobalt oxide to the second lithium cobalt oxide is (1.5-4.0): 1. By controlling the mixing ratio and the mixing sequence of the lithium cobalt oxides and the lithium titanium aluminum phosphate with different particle sizes, the obtained composite lithium cobalt oxide positive electrode material has high compaction density and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of lithium-ion batteries, and more specifically, to a composite lithium cobalt oxide positive electrode material, a preparation method thereof, a positive electrode sheet and a lithium-ion battery. Background Art

[0002] High energy density (ED) is the research direction of most secondary batteries, and high rate is also a performance that must be considered for consumer batteries. For positive electrode materials, high ED often corresponds to high voltage, high compaction density (PD) and high tap density (TD), while high rate corresponds to high specific surface area (BET), low compaction density and low tap density.

[0003] That is to say, from the material side itself, it is difficult to improve both energy density and rate performance at the same time. Compared with other positive electrode materials, lithium cobalt oxide has a higher compaction density, higher voltage, and better rate performance. When producing lithium cobalt oxide, the particle size of lithium cobalt oxide can generally be controlled by regulating the process. Capacitive lithium cobalt oxide with larger particle size often has a larger tap density and compaction density, a smaller BET, and poorer rate performance; rate-type lithium cobalt oxide with smaller particle size often has a smaller tap density and compaction density, a larger BET, and better rate performance.

[0004] In order to further improve the energy density of lithium cobalt oxide cathode materials, it is necessary to increase their compaction density. The means to increase the compaction density of cathode materials is generally to increase the particle size, which will inevitably reduce the specific surface area of ​​the material. In addition, the migration of lithium ions is hindered under high compaction, making it difficult for the battery to meet the 5C discharge requirement. For example, the compaction density of current capacity-type lithium cobalt oxide materials can reach 4.2g / cm 3 , which can bring higher energy density, but at the same time its rate performance is only below 3C. For example, CN116768282B provides a high-rate lithium cobalt oxide, the discharge capacity of the full battery prepared with this lithium cobalt oxide at 4.45V, 20C is more than 95% of that at 0.2C, but its compaction density is only 3.7-3.9g / cm 3 CN114220645A provides a lithium cobalt oxide with a bimodal particle size distribution and a compacted density of 4.1 g / cm 3 , but this material is only suitable for a voltage of 4.45V, and the larger particle size distribution will lead to a loss in rate performance.

[0005] Based on this, how to balance the density and specific surface area of ​​lithium cobalt oxide so that it can have both high energy density and excellent rate performance when used as a positive electrode material is one of the important technical problems that need to be solved in this field. Summary of the invention

[0006] The main purpose of the present application is to provide a composite lithium cobalt oxide positive electrode material, a preparation method thereof, a positive electrode plate and a lithium ion battery, so as to solve the problem that the lithium cobalt oxide positive electrode material in the prior art is difficult to achieve both high energy density and excellent rate performance.

[0007] In order to achieve the above-mentioned objectives, the first aspect of the present application provides a composite lithium cobalt oxide positive electrode material, including: a first lithium cobalt oxide with a D50 of 13μm to 16μm, a second lithium cobalt oxide with a D50 of 5.5μm to 6.5μm, a first lithium aluminum titanium phosphate with a D50 of 300nm to 500nm, and a second lithium aluminum titanium phosphate with a D50 of 100nm to 280nm; the weight ratio of the first lithium cobalt oxide to the first lithium aluminum titanium phosphate is (100 to 300):1; the weight ratio of the second lithium cobalt oxide to the second lithium aluminum titanium phosphate is (100 to 300):1; the weight ratio of the first lithium cobalt oxide to the second lithium aluminum titanium phosphate is (100 to 300):1; the weight ratio of the first lithium cobalt oxide to the second lithium cobalt oxide is (1.5 to 4.0):1.

[0008] Furthermore, the molecular formulas of the first lithium aluminum titanium phosphate and the second lithium aluminum titanium phosphate are independently Li 1+ x A1 x Ti 2-x (PO4)3, where 0.01≤x<1.

[0009] Further, D10 of the first lithium cobaltate is 4.8 μm to 6.5 μm, and D10 of the second lithium cobaltate is 3.0 μm to 4.0 μm; and / or D90 of the first lithium cobaltate is 25.0 μm to 28.0 μm, and D90 of the second lithium cobaltate is 10.0 μm to 12.0 μm.

[0010] Furthermore, the specific particle size distribution value (D90-D10) / D50 of the first lithium cobaltate is 1.25-1.55, and the specific particle size distribution value (D90-D10) / D50 of the second lithium cobaltate is 1.00-1.20.

[0011] Furthermore, the tap density of the first lithium cobalt oxide is 2.7 g / cm 3 ~3.0g / cm 3 The tap density of the second lithium cobalt oxide is 2.0g / cm 3 ~2.6g / cm 3 ; and / or, the specific surface area of ​​the first lithium cobaltate is 0.15m 2 / g~0.25m 2 / g, the specific surface area of ​​the second lithium cobalt oxide is 0.35m 2 / g~0.50m 2 / g.

[0012] Furthermore, the specific surface area of ​​the composite lithium cobalt oxide positive electrode material is 0.25m 2 / g~0.35m 2 / g, tap density is 2.5g / cm 3 ~2.8g / cm 3 Furthermore, the D10 of the composite lithium cobalt oxide positive electrode material is 3.8μm~5.0μm, D50 is 11.4μm~12.9μm, D90 is 24.8μm~27.7μm, and the specific particle size distribution value (D90-D10) / D50 is 1.6~2.1.

[0013] The second aspect of the present application provides a method for preparing the above-mentioned composite lithium cobalt oxide positive electrode material, comprising: step S1, mixing the first lithium cobalt oxide and the first lithium aluminum titanium phosphate for the first time to obtain the first composite lithium cobalt oxide; step S2, mixing the second lithium cobalt oxide and the second lithium aluminum titanium phosphate for the second time to obtain the second composite lithium cobalt oxide; step S3, mixing the first composite lithium cobalt oxide and the second composite lithium cobalt oxide for the third time to obtain the composite lithium cobalt oxide positive electrode material.

[0014] Furthermore, the first mixing, the second mixing and the third mixing are all achieved by a batch mixer, and the spindle frequency of the batch mixer used for the first mixing, the second mixing and the third mixing is independently 20 Hz to 60 Hz, and the mixing time is independently 1 h to 5 h.

[0015] The third aspect of the present application provides a positive electrode plate, which includes the above-mentioned composite lithium cobalt oxide positive electrode material.

[0016] A fourth aspect of the present application provides a lithium-ion battery, which includes the above-mentioned positive electrode plate.

[0017] By applying the technical solution of the present application, by finely controlling the mixing ratio and mixing order of lithium cobalt oxide with different particle sizes and lithium aluminum titanium phosphate, the obtained composite lithium cobalt oxide positive electrode material can have both high density and high specific surface area, and ultimately improve its electrochemical performance, including improving specific capacity, cycle stability and rate performance. The prepared composite lithium cobalt oxide positive electrode material has an optimized particle size distribution and physical properties, which can significantly improve the energy density of lithium-ion batteries and increase their cycle life at high rates. DETAILED DESCRIPTION

[0018] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below in conjunction with the embodiments.

[0019] As described in the background technology, the lithium cobalt oxide positive electrode material in the prior art has the problem of being difficult to balance high energy density and excellent rate performance. In order to solve the above technical problems, the first aspect of the present application provides a composite lithium cobalt oxide positive electrode material, including: a first lithium cobalt oxide with a D50 of 13μm to 16μm, a second lithium cobalt oxide with a D50 of 5.5μm to 6.5μm, a first lithium titanium aluminum phosphate with a D50 of 300nm to 500nm, and a second lithium titanium aluminum phosphate with a D50 of 100nm to 280nm; the weight ratio of the first lithium cobalt oxide to the first lithium titanium aluminum phosphate is (100 to 300): 1; the weight ratio of the second lithium cobalt oxide to the second lithium titanium aluminum phosphate is (100 to 300): 1; the weight ratio of the first lithium cobalt oxide to the second lithium titanium aluminum phosphate is (100 to 300): 1; the weight ratio of the first lithium cobalt oxide to the second lithium cobalt oxide is (1.5 to 4.0): 1.

[0020] By carefully designing and strictly limiting the particle size matching relationship of each component of the composite lithium cobalt oxide material, the particle size distribution is optimized and the physical and chemical properties are improved. In particular, the resulting composite lithium cobalt oxide positive electrode material can have both high density and high specific surface area, thereby exhibiting excellent electrochemical properties.

[0021] What is indispensable is that the above-mentioned material component formula strictly limits the particle size range of the two types of lithium cobalt oxide and the two types of lithium aluminum titanium phosphate, so that the doping can be carried out more effectively, and the composite lithium cobalt oxide with significantly improved rate performance can be obtained. In addition, the particle size combination of the above-mentioned lithium cobalt oxide and lithium aluminum titanium phosphate can further enhance the structural stability while optimizing the rate performance of the obtained composite lithium cobalt oxide. In addition, by strictly controlling the weight ratio of the first lithium cobalt oxide to the second lithium cobalt oxide to (1.5-4.0): 1, the particle size, density and specific surface area of ​​the obtained composite lithium cobalt oxide positive electrode material can be balanced, so that it can take into account both high density and specific surface area, and then make it have both high energy density and rate performance when used as a positive electrode material. At the same time, this weight relationship can also balance the electrochemical properties and processing properties of the obtained positive electrode material, ensure its uniformity and stability in subsequent applications, and thus improve the consistency and safety of the battery in which it is located.

[0022] In order to more significantly exert the gain effect of the first lithium aluminum titanium phosphate and the second lithium aluminum titanium phosphate on the rate performance of the obtained composite lithium cobalt oxide material, the weight ratio of the first lithium cobalt oxide to the first lithium aluminum titanium phosphate is limited to (100-300): 1; the weight ratio of the second lithium cobalt oxide to the second lithium aluminum titanium phosphate is (100-300): 1. These two ratios can not only effectively improve the cycle performance and high-rate discharge capability of lithium cobalt oxide, but also protect its intrinsic particle size distribution characteristics, thereby obtaining a composite lithium cobalt oxide positive electrode material with excellent comprehensive performance.

[0023] That is to say, the above-mentioned composite lithium cobalt oxide positive electrode material provided in the present application has optimized particle size distribution and physical properties, which can significantly improve the energy density of the lithium-ion battery in which it is located, while increasing its cycle life at high rates.

[0024] Further, based on the improvement of the rate performance that lithium aluminum titanium phosphate can provide to lithium cobalt oxide, the molecular formulas of the first lithium aluminum titanium phosphate and the second lithium aluminum titanium phosphate are independently Li 1+x A1 x Ti 2-x (PO4)3, where 0.01≤x<1, so as to better match the molecular structure of the first lithium cobalt oxide and the second lithium cobalt oxide material, optimize the ion transmission path, and improve the rate performance of the lithium cobalt oxide material after the two are mixed. On this basis, the inventors further made x in the molecular formula 0.2-0.4 through a large number of experiments, thereby obtaining a higher lithium ion diffusion rate and making the electrochemical performance of the resulting composite lithium cobalt oxide material more superior.

[0025] In order to more effectively coordinate the physicochemical properties of the two lithium cobalt oxide materials, obtain a composite lithium cobalt oxide material with a more suitable particle size, and then make the obtained composite lithium cobalt oxide positive electrode material show a higher energy density, further, the D10 of the first lithium cobalt oxide is 4.8μm to 6.5μm, and the D10 of the second lithium cobalt oxide is 3.0μm to 4.0μm; and / or, the D90 of the first lithium cobalt oxide is 25.0μm to 28.0μm, and the D90 of the second lithium cobalt oxide is 10.0μm to 12.0μm. And, in the matching relationship of the above particle size range, in some embodiments, the specific particle size distribution value (D90-D10) / D50 of the first lithium cobalt oxide is 1.25 to 1.55, and the specific particle size distribution value (D90-D10) / D50 of the second lithium cobalt oxide is 1.00 to 1.20, so as to achieve a comprehensive improvement in the density and specific surface area of ​​the positive electrode material by optimizing the particle size distribution of the two lithium cobalt oxides. At the same time, it can also more effectively avoid agglomeration, thereby more effectively improving the high energy density of the resulting composite lithium cobalt oxide positive electrode material in subsequent applications, as well as the long cycle life at high rates.

[0026] Furthermore, in order to more effectively balance the density and specific surface area of ​​the obtained composite lithium cobalt oxide positive electrode material, thereby effectively improving its energy density as a positive electrode material for lithium ion batteries and its performance under high rate conditions, the inventors conducted a large number of experiments and made the tap density of the first lithium cobalt oxide 2.7g / cm 3 ~3.0g / cm 3 The tap density of the second lithium cobalt oxide is 2.0g / cm 3 ~2.6g / cm 3 ; and / or, the specific surface area of ​​the first lithium cobaltate is 0.15m 2 / g~0.25m2 / g, the specific surface area of ​​the second lithium cobalt oxide is 0.35m 2 / g~0.50m 2 / g.

[0027] In some embodiments, the specific surface area of ​​the composite lithium cobalt oxide positive electrode material is 0.25 m 2 / g~0.35m 2 / g, tap density is 2.5g / cm 3 ~2.8g / cm 3 ; Further, the D10 of the composite lithium cobalt oxide positive electrode material is 3.8μm to 5.0μm, the D50 is 11.4μm to 12.9μm, the D90 is 24.8μm to 27.7μm, and the specific particle size distribution value (D90-D10) / D50 is 1.6 to 2.1. In other words, the composite lithium cobalt oxide positive electrode material provided in this application has excellent physical and chemical properties and particle size distribution, and can be used as a positive electrode material in a battery to achieve efficient energy storage and release, while maintaining good cycle stability and safety.

[0028] The second aspect of the present application provides a method for preparing the above-mentioned composite lithium cobalt oxide positive electrode material, comprising: step S1, mixing the first lithium cobalt oxide and the first lithium aluminum titanium phosphate for the first time to obtain the first composite lithium cobalt oxide; step S2, mixing the second lithium cobalt oxide and the second lithium aluminum titanium phosphate for the second time to obtain the second composite lithium cobalt oxide; step S3, mixing the first composite lithium cobalt oxide and the second composite lithium cobalt oxide for the third time to obtain the composite lithium cobalt oxide positive electrode material.

[0029] Compared with the method of blending two types of lithium titanium aluminum phosphates into the lithium cobalt oxide material system, the mixing order based on the particle size matching relationship provided in the present application can ensure the uniformity of the dispersion of lithium titanium aluminum phosphate during the entire preparation process of the composite lithium cobalt oxide material, thereby making the resulting positive electrode material exhibit better electrochemical properties, including high energy density, rate performance and cycle stability.

[0030] In several typical embodiments, in order to achieve an improvement in the intrinsic rate performance of the first composite lithium cobalt oxide and the second composite lithium cobalt oxide, and to enable the two to obtain a composite lithium cobalt oxide positive electrode material with better comprehensive performance at a higher efficiency when mixed, the first mixing, the second mixing and the third mixing are all achieved by a batch mixer, and the spindle frequencies of the batch mixers used for the first mixing, the second mixing and the third mixing are each independently 20 Hz to 60 Hz, and the mixing time is each independently 1 h to 5 h.

[0031] In several more typical embodiments, the inventors screened the corresponding condition parameters in the three mixing processes through a large number of experiments, and obtained: the spindle frequency of the batch mixer used for the first mixing is 50Hz~60Hz, and the mixing time is 4h~5h; and / or, the spindle frequency of the batch mixer used for the second mixing is 20Hz~30Hz, and the mixing time is 1h~2h; and / or, the spindle frequency of the batch mixer used for the third mixing is 35Hz~45Hz, and the mixing time is 2.5h~3.5h. Through the above-mentioned more accurate mixing parameter setting, the material particle size in each mixing process can be further and separately adapted, so that the mixing of the first lithium aluminum titanium phosphate and the first lithium cobaltate, the second lithium aluminum titanium phosphate and the second lithium cobaltate, and the first composite lithium cobaltate and the second composite lithium cobaltate is more efficient, and the uniformity after mixing is also improved. As a result, the microscopic morphology, particle size and distribution, and physical properties such as density of the obtained material are more effectively optimized, and its comprehensive electrochemical performance is improved, so as to obtain a composite lithium cobaltate positive electrode material with greater energy density and better rate performance.

[0032] The third aspect of the present application provides a positive electrode plate, which includes the above-mentioned composite lithium cobalt oxide positive electrode material. The above-mentioned positive electrode material has both high density and high specific surface area, so that the positive electrode plate in which it is located can have better comprehensive performance.

[0033] The fourth aspect of the present application provides a lithium-ion battery, which includes the above-mentioned positive electrode plate. Since the positive electrode material in the positive electrode plate obtained in the present application has superior performance, the lithium-ion battery in which it is located exhibits higher energy density and higher rate performance, and also has excellent cycle stability.

[0034] In several preferred embodiments, at 25°C and 4.5V, the capacity retention rate of the obtained lithium-ion battery is 77.5% to 84.5%, and the compaction density of the composite lithium cobalt oxide positive electrode material in the positive electrode sheet of the lithium-ion battery is 4.0g / cm 3 That is to say, when the composite lithium cobalt oxide positive electrode material obtained in the present invention is used to prepare a positive electrode sheet with a high compaction density, the lithium ion battery in which the obtained positive electrode sheet is located can still maintain high cycle stability.

[0035] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0036] Unless otherwise defined, all professional terms used below have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of this application.

[0037] Example 1

[0038] A method for preparing a composite lithium cobalt oxide positive electrode material:

[0039] Material description: The D10, D50, D90, specific particle size distribution value (D90-D10) / D50, tap density and specific surface area parameters of the first lithium cobalt oxide used are shown in Table 1. The D10, D50, D90, specific particle size distribution value (D90-D10) / D50, tap density and specific surface area parameters of the second lithium cobalt oxide used are also shown in Table 1.

[0040] The molecular formula is Li 1+x A1 x Ti 2-x The lithium aluminum titanium phosphate material of (PO4)3 (wherein x is 0.3) is used as the first lithium aluminum titanium phosphate and the second lithium aluminum titanium phosphate, respectively, and the D50 of the first lithium aluminum titanium phosphate and the second lithium aluminum titanium phosphate are shown in Table 1-1.

[0041] Table 1-1

[0042] D10 D50 D90 (D90-D10) / D50 Tap density Specific surface area First lithium cobalt oxide 6.44μm 15.14μm 27.96μm 1.42 <![CDATA[2.83g / cm 3 ]]> <![CDATA[0.22m 2 / g]]> First Lithium Aluminum Titanium Phosphate \ 500nm \ \ \ \ Second lithium cobalt oxide 3.76μm 6.49μm 10.99μm 1.11 <![CDATA[2.38g / cm 3 ]]> <![CDATA[0.38m 2 / g]]> Second lithium aluminum titanium phosphate \ 100nm \ \ \ \

[0043] Method steps:

[0044] (1) using a batch mixer, mixing the first lithium cobalt oxide and the first lithium aluminum titanium phosphate in a weight ratio of 100:1, the main shaft frequency of the batch mixer during mixing is 60 Hz, and the mixing time is 5 hours to obtain a first composite lithium cobalt oxide;

[0045] (2) using a batch mixer, mixing the second lithium cobalt oxide and the second lithium aluminum titanium phosphate in a weight ratio of 100:1, the main shaft frequency of the batch mixer during mixing is 20 Hz, and the mixing time is 1 hour, to obtain a second composite lithium cobalt oxide;

[0046] (3) Under the condition that the weight ratio of the first lithium cobalt oxide to the second lithium cobalt oxide is 7:3, the first composite lithium cobalt oxide and the second composite lithium cobalt oxide are mixed for the third time by a batch mixer, the main shaft frequency of the batch mixer during mixing is 40 Hz, and the mixing time is 3 hours, thereby obtaining a composite lithium cobalt oxide positive electrode material.

[0047] Example 2

[0048] A method for preparing a composite lithium cobalt oxide positive electrode material:

[0049] The difference between this embodiment and embodiment 1 is only in the method steps, specifically:

[0050] (1) using a batch mixer, mixing the first lithium cobalt oxide and the first lithium aluminum titanium phosphate in a weight ratio of 300:1, the main shaft frequency of the batch mixer during mixing is 50 Hz, and the mixing time is 4 hours to obtain a first composite lithium cobalt oxide;

[0051] (2) using a batch mixer, mixing the second lithium cobalt oxide and the second lithium aluminum titanium phosphate in a weight ratio of 300:1, the main shaft frequency of the batch mixer during mixing is 20 Hz, and the mixing time is 1 hour, to obtain a second composite lithium cobalt oxide;

[0052] (3) Under the condition that the weight ratio of the first lithium cobalt oxide to the second lithium cobalt oxide is 4:1, the first composite lithium cobalt oxide and the second composite lithium cobalt oxide are mixed for the third time by a batch mixer, the main shaft frequency of the batch mixer during mixing is 35 Hz, and the mixing time is 3.5 hours, thereby obtaining a composite lithium cobalt oxide positive electrode material.

[0053] Example 3

[0054] A method for preparing a composite lithium cobalt oxide positive electrode material:

[0055] The difference between this embodiment and embodiment 1 is only in the method steps, specifically:

[0056] (1) using a batch mixer, mixing the first lithium cobalt oxide and the first lithium aluminum titanium phosphate in a weight ratio of 100:1, the main shaft frequency of the batch mixer during mixing is 60 Hz, and the mixing time is 5 hours to obtain a first composite lithium cobalt oxide;

[0057] (2) using a batch mixer, mixing the second lithium cobalt oxide and the second lithium aluminum titanium phosphate in a weight ratio of 100:1, the main shaft frequency of the batch mixer during mixing is 20 Hz, and the mixing time is 2 hours to obtain a second composite lithium cobalt oxide;

[0058] (3) Under the condition that the weight ratio of the first lithium cobalt oxide to the second lithium cobalt oxide is 1.5:1, the first composite lithium cobalt oxide and the second composite lithium cobalt oxide are mixed for the third time by a batch mixer, the main shaft frequency of the batch mixer during mixing is 45 Hz, and the mixing time is 2.5 hours, thereby obtaining a composite lithium cobalt oxide positive electrode material.

[0059] Example 4

[0060] A method for preparing a composite lithium cobalt oxide positive electrode material:

[0061] The difference between this embodiment and embodiment 1 is only the type of raw materials, see Table 1-2 for details.

[0062] Table 1-2

[0063] D10 D50 D90 (D90-D10) / D50 Tap density Specific surface area First lithium cobalt oxide 6.44μm 15.14μm 27.96μm 1.42 <![CDATA[2.83g / cm 3 ]]> <![CDATA[0.22m 2 / g]]> First Lithium Aluminum Titanium Phosphate \ 500nm \ \ \ \ Second lithium cobalt oxide 3.36μm 5.96μm 10.04μm 1.12 <![CDATA[2.04g / cm 3 ]]> <![CDATA[0.47m 2 / g]]> Second lithium aluminum titanium phosphate \ 250nm \ \ \ \

[0064] Example 5

[0065] A method for preparing a composite lithium cobalt oxide positive electrode material:

[0066] The difference between this embodiment and embodiment 1 is only the type of raw materials, see Table 1-3 for details.

[0067] Table 1-3

[0068] D10 D50 D90 (D90-D10) / D50 Tap density Specific surface area First lithium cobalt oxide 5.03μm 15.92μm 25.04μm 1.25 <![CDATA[2.87g / cm 3 ]]> <![CDATA[0.24m 2 / g]]> First Lithium Aluminum Titanium Phosphate \ 300nm \ \ \ \ Second lithium cobalt oxide 3.76μm 6.49μm 10.99μm 1.11 <![CDATA[2.38g / cm 3 ]]> <![CDATA[0.38m 2 / g]]> Second lithium aluminum titanium phosphate \ 100nm \ \ \ \

[0069] Example 6

[0070] A method for preparing a composite lithium cobalt oxide positive electrode material:

[0071] The only difference between this embodiment and embodiment 1 is that in the preparation step, the first lithium cobaltate, the second lithium cobaltate, the first lithium aluminum titanium phosphate and the second lithium aluminum titanium phosphate are mixed in the same weight ratio as in embodiment 1, the spindle frequency of the batch mixer during mixing is 40 Hz, and the mixing time is 3 hours, so as to obtain a composite lithium cobaltate positive electrode material.

[0072] Example 7

[0073] A method for preparing a composite lithium cobalt oxide positive electrode material:

[0074] The difference between this embodiment and embodiment 1 is that the molecular formula of the first lithium aluminum titanium phosphate and the second lithium aluminum titanium phosphate are changed to Li 1+x A1 x Ti 2-x In (PO4)3, the value of x is 0.8.

[0075] Example 8

[0076] A method for preparing a composite lithium cobalt oxide positive electrode material:

[0077] The difference between this embodiment and embodiment 1 is that the molecular formula of the first lithium aluminum titanium phosphate and the second lithium aluminum titanium phosphate are changed to Li 1+x A1 x Ti 2-x In (PO4)3, the value of x is 0.01.

[0078] Example 9

[0079] A method for preparing a composite lithium cobalt oxide positive electrode material:

[0080] The difference between this embodiment and embodiment 1 is only the type of raw materials, see Table 1-4 for details.

[0081] Table 1-4

[0082] D10 D50 D90 (D90-D10) / D50 Tap density Specific surface area First lithium cobalt oxide 4.52μm 13.09μm 30.45μm 1.98 <![CDATA[2.65g / cm 3 ]]> <![CDATA[0.39m 2 / g]]> First Lithium Aluminum Titanium Phosphate \ 300nm \ \ \ \ Second lithium cobalt oxide 3.76μm 6.49μm 10.99μm 1.11 <![CDATA[2.38g / cm 3 ]]> <![CDATA[0.38m 2 / g]]> Second lithium aluminum titanium phosphate \ 100nm \ \ \ \

[0083] Example 10

[0084] A method for preparing a composite lithium cobalt oxide positive electrode material:

[0085] The difference between this embodiment and embodiment 1 is only the type of raw materials, see Table 1-5 for details.

[0086] Table 1-5

[0087] D10 D50 D90 (D90-D10) / D50 Tap density Specific surface area First lithium cobalt oxide 6.44μm 15.14μm 27.96μm 1.42 <![CDATA[2.83g / cm 3 ]]> <![CDATA[0.22m 2 / g]]> First Lithium Aluminum Titanium Phosphate \ 500nm \ \ \ \ Second lithium cobalt oxide 2.37μm 5.53μm 13.76μm 1.28 <![CDATA[1.97g / cm 3 ]]> <![CDATA[0.52m 2 / g]]> Second lithium aluminum titanium phosphate \ 100nm \ \ \ \

[0088] Embodiment 11

[0089] A method for preparing a composite lithium cobalt oxide positive electrode material:

[0090] The difference between this embodiment and embodiment 1 is only in the method steps, specifically:

[0091] (1) using a batch mixer, mixing the first lithium cobalt oxide and the first lithium aluminum titanium phosphate in a weight ratio of 100:1, the main shaft frequency of the batch mixer during mixing is 70 Hz, and the mixing time is 3 hours to obtain a first composite lithium cobalt oxide;

[0092] (2) using a batch mixer, mixing the second lithium cobalt oxide and the second lithium aluminum titanium phosphate in a weight ratio of 100:1, the main shaft frequency of the batch mixer during mixing is 40 Hz, and the mixing time is 0.5 h, to obtain a second composite lithium cobalt oxide;

[0093] (3) Under the condition that the weight ratio of the first lithium cobalt oxide to the second lithium cobalt oxide is 7:3, the first composite lithium cobalt oxide and the second composite lithium cobalt oxide are mixed for the third time by a batch mixer, the main shaft frequency of the batch mixer during mixing is 50 Hz, and the mixing time is 2 hours, thereby obtaining a composite lithium cobalt oxide positive electrode material.

[0094] In this embodiment, the stirring frequency is relatively high, which may cause the lithium cobalt oxide particles and the lithium aluminum titanium phosphate particles to break during the mixing process, thereby causing a decrease in performance.

[0095] Example 12

[0096] A method for preparing a composite lithium cobalt oxide positive electrode material:

[0097] The difference between this embodiment and embodiment 1 is only in the method steps, specifically:

[0098] (1) using a batch mixer, mixing the first lithium cobalt oxide and the first lithium aluminum titanium phosphate in a weight ratio of 100:1, the main shaft frequency of the batch mixer during mixing is 50 Hz, and the mixing time is 6 hours to obtain a first composite lithium cobalt oxide;

[0099] (2) using a batch mixer, mixing the second lithium cobalt oxide and the second lithium aluminum titanium phosphate in a weight ratio of 100:1, the main shaft frequency of the batch mixer during mixing is 10 Hz, and the mixing time is 3 hours to obtain a second composite lithium cobalt oxide;

[0100] (3) Under the condition that the weight ratio of the first lithium cobalt oxide to the second lithium cobalt oxide is 7:3, the first composite lithium cobalt oxide and the second composite lithium cobalt oxide are mixed for the third time by a batch mixer, the main shaft frequency of the batch mixer during mixing is 30 Hz, and the mixing time is 4 hours, thereby obtaining a composite lithium cobalt oxide positive electrode material.

[0101] In this embodiment, the stirring frequency is low and the mixing time is long, which may cause micro-agglomeration of the lithium aluminum titanium phosphate particles during the mixing process, resulting in a decrease in the rate performance.

[0102] Comparative Example 1

[0103] A method for preparing a composite lithium cobalt oxide positive electrode material:

[0104] The difference between this comparative example and Example 1 is only the type of raw materials, as shown in Table 1-6.

[0105] Table 1-6

[0106] D10 D50 D90 (D90-D10) / D50 Tap density Specific surface area First lithium cobalt oxide 7.21μm 17.15μm 29.64μm 1.31 <![CDATA[2.93g / cm 3 ]]> <![CDATA[0.18m 2 / g]]> First Lithium Aluminum Titanium Phosphate \ 600nm \ \ \ \ Second lithium cobalt oxide 3.76μm 6.49μm 10.99μm 1.11 <![CDATA[2.38g / cm 3 ]]> <![CDATA[0.38m 2 / g]]> Second lithium aluminum titanium phosphate \ 100nm \ \ \ \

[0107] Comparative Example 2

[0108] A method for preparing a composite lithium cobalt oxide positive electrode material:

[0109] The difference between this comparative example and Example 1 is only the type of raw materials, as shown in Table 1-7.

[0110] Table 1-7

[0111] D10 D50 D90 (D90-D10) / D50 Tap density Specific surface area First lithium cobalt oxide 6.44μm 15.14μm 27.96μm 1.42 <![CDATA[2.83g / cm 3 ]]> <![CDATA[0.22m 2 / g]]> First Lithium Aluminum Titanium Phosphate \ 500nm \ \ \ \ Second lithium cobalt oxide 4.65μm 8.05μm 12.46μm 0.97 <![CDATA[2.58g / cm 3 ]]> <![CDATA[0.33m 2 / g]]> Second lithium aluminum titanium phosphate \ 50nm \ \ \ \

[0112] Comparative Example 3

[0113] A method for preparing a composite lithium cobalt oxide positive electrode material:

[0114] The difference between this comparative example and Example 1 is that in step (3), the first composite lithium cobalt oxide and the second composite lithium cobalt oxide are mixed at a weight ratio of 1:1 between the first lithium cobalt oxide and the second lithium cobalt oxide.

[0115] Comparative Example 4

[0116] A method for preparing a composite lithium cobalt oxide positive electrode material:

[0117] The difference between this comparative example and Example 1 is that in step (3), the first composite lithium cobalt oxide and the second composite lithium cobalt oxide are mixed at a weight ratio of 5:1 between the first lithium cobalt oxide and the second lithium cobalt oxide.

[0118] Comparative Example 5

[0119] A method for preparing a composite lithium cobalt oxide positive electrode material:

[0120] The difference between this comparative example and Example 1 is that in the preparation step, steps (1) and (2) are not performed, but the first lithium cobalt oxide and the second lithium cobalt oxide are directly mixed in a weight ratio of 7:3 by a batch mixer, the main shaft frequency of the batch mixer during mixing is 40 Hz, and the mixing time is 3 hours, so as to obtain a composite lithium cobalt oxide positive electrode material.

[0121] That is, this comparative example does not introduce lithium aluminum titanium phosphate material.

[0122] Comparative Example 6

[0123] A method for preparing a composite lithium cobalt oxide positive electrode material:

[0124] The difference between this comparative example and Example 1 is only in the method steps, specifically:

[0125] (1) using a batch mixer, mixing the first lithium cobalt oxide and the first lithium aluminum titanium phosphate in a weight ratio of 50:1, with the main shaft frequency of the batch mixer being 60 Hz and the mixing time being 5 hours, to obtain a first composite lithium cobalt oxide;

[0126] (2) using a batch mixer, mixing the second lithium cobalt oxide and the second lithium aluminum titanium phosphate in a weight ratio of 400:1, the main shaft frequency of the batch mixer during mixing is 20 Hz, and the mixing time is 1 hour, to obtain a second composite lithium cobalt oxide;

[0127] (3) Under the condition that the weight ratio of the first lithium cobalt oxide to the second lithium cobalt oxide is 7:3, the first composite lithium cobalt oxide and the second composite lithium cobalt oxide are mixed for the third time by a batch mixer, the main shaft frequency of the batch mixer during mixing is 40 Hz, and the mixing time is 3 hours, thereby obtaining a composite lithium cobalt oxide positive electrode material.

[0128] Test Method

[0129] D10, D50, D90 and specific particle size distribution value SPAN ((D90-D10) / D50): all obtained through GB19077 test.

[0130] Tap density: obtained by testing according to GB / T 5162-2021.

[0131] Specific surface area: obtained through GB / T 19587 test.

[0132] Battery sample preparation and performance testing:

[0133] (1) Preparation of positive electrode sheet: The composite lithium cobalt oxide positive electrode material obtained in each embodiment and comparative example was prepared into positive electrode slurry, and aluminum foil was used as the current collector. The compaction density of each sample was controlled to be 4.0 g / cm 3 , prepare the positive electrode. (2) Assembly of battery samples: copper foil is used as the negative electrode, PP diaphragm with a thickness of 12μm is used as the battery diaphragm, and 15% LiPF6+FEC+HTCN+EC / PC / DEC / EP / PP electrolyte system is used as the battery electrolyte to assemble a soft pack battery sample with a capacity of 2100mAh. (3) Performance test: Under the conditions of 25℃ and 4.5V, 1C charge and 5C discharge, cycle 800 times, and test the capacity retention rate of each battery sample. The larger the value, the better the cycle stability of the battery sample under high rate conditions, that is, it has a higher rate performance.

[0134] The results of the above tests are shown in Table 2.

[0135] Table 2

[0136]

[0137]

[0138] From the above description, it can be seen that the above-mentioned embodiment of the present application realizes the preparation of a composite lithium cobalt oxide material with both high density and high specific surface area. When it is used as a positive electrode material in a lithium ion battery, the obtained lithium ion battery sample has good rate performance, and under the conditions of 1C charging and 5C discharging, it can still show excellent long-cycle stability after 800 cycles.

[0139] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0140] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A composite lithium cobalt oxide positive electrode material, characterized in that: include: A first lithium cobalt oxide having a D50 of 13 μm to 16 μm, a second lithium cobalt oxide having a D50 of 5.5 μm to 6.5 μm, a first lithium aluminum titanium phosphate having a D50 of 300 nm to 500 nm, and a second lithium aluminum titanium phosphate having a D50 of 100 nm to 280 nm; The weight ratio of the first lithium cobaltate to the first lithium aluminum titanium phosphate is (100-300):1; The weight ratio of the second lithium cobaltate to the second lithium aluminum titanium phosphate is (100-300):1; The weight ratio of the first lithium cobalt oxide to the second lithium cobalt oxide is (1.5-4.0):

1.

2. The composite lithium cobalt oxide positive electrode material according to claim 1, characterized in that: The molecular formulas of the first lithium aluminum titanium phosphate and the second lithium aluminum titanium phosphate are independently Li 1+x A1 x Ti 2-x (PO4)3, where 0.01≤x<1.

3. The composite lithium cobalt oxide positive electrode material according to claim 1 or 2, characterized in that: The D10 of the first lithium cobalt oxide is 4.8 μm to 6.5 μm, and the D10 of the second lithium cobalt oxide is 3.0 μm to 4.0 μm; and / or the D90 of the first lithium cobalt oxide is 25.0 μm to 28.0 μm, and the D90 of the second lithium cobalt oxide is 10.0 μm to 12.0 μm.

4. The composite lithium cobalt oxide positive electrode material according to any one of claims 1 to 3, characterized in that: The specific particle size distribution value (D90-D10) / D50 of the first lithium cobaltate is 1.25-1.55, and the specific particle size distribution value (D90-D10) / D50 of the second lithium cobaltate is 1.00-1.

20.

5. The composite lithium cobalt oxide positive electrode material according to any one of claims 1 to 4, characterized in that: The tap density of the first lithium cobalt oxide is 2.7 g / cm 3 ~3.0g / cm 3 The tap density of the second lithium cobalt oxide is 2.0 g / cm 3 ~2.6g / cm 3 and / or, The specific surface area of ​​the first lithium cobalt oxide is 0.15 m 2 / g~0.25m 2 / g, the specific surface area of ​​the second lithium cobaltate is 0.35m 2 / g~0.50m 2 / g.

6. The composite lithium cobalt oxide positive electrode material according to any one of claims 1 to 5, characterized in that: The specific surface area of ​​the composite lithium cobalt oxide positive electrode material is 0.25 m 2 / g~0.35m 2 / g, tap density is 2.5g / cm 3 ~2.8g / cm 3 ; Preferably, the D10 of the composite lithium cobalt oxide positive electrode material is 3.8 μm to 5.0 μm, the D50 is 11.4 μm to 12.9 μm, the D90 is 24.8 μm to 27.7 μm, and the specific particle size distribution value (D90-D10) / D50 is 1.6 to 2.

1.

7. A method for preparing the composite lithium cobalt oxide positive electrode material according to any one of claims 1 to 6, characterized in that: include: Step S1, performing a first mixing of the first lithium cobalt oxide and the first lithium aluminum titanium phosphate to obtain a first composite lithium cobalt oxide; Step S2, performing a second mixing of the second lithium cobalt oxide and the second lithium aluminum titanium phosphate to obtain a second composite lithium cobalt oxide; Step S3: performing a third mixing of the first composite lithium cobalt oxide and the second composite lithium cobalt oxide to obtain the composite lithium cobalt oxide positive electrode material.

8. The preparation method according to claim 7, characterized in that: The first mixing, the second mixing and the third mixing are all achieved by a batch mixer, and the spindle frequencies of the batch mixers used for the first mixing, the second mixing and the third mixing are independently 20 Hz to 60 Hz, and the mixing times are independently 1 h to 5 h.

9. A positive electrode sheet, characterized in that: The positive electrode plate comprises the composite lithium cobalt oxide positive electrode material according to any one of claims 1 to 6.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Preparation method of amorphous composite magnetic powder core

    CN114220645A

  • Composite anode material for lithium battery, and preparation method of composite anode material

    CN109786679A

  • Li1+xAlxTi2-x (PO3)4-coated lithium cobalt oxide material and preparation method and application thereof

    CN109994722A

  • Lithium battery composite positive electrode material and preparation method thereof

    CN112310354A

  • Lithium cobalt oxide composite material as well as preparation method and application thereof

    CN112713267A

Cited By

  • Composite lithium cobalt oxide positive electrode material and preparation method therefor, positive electrode sheet, and lithium ion battery

    WO2026137938A1